IMPROVING WRITING SKILLS THROUGH THE DUOLINGO APPLICATION - Adelia Eka Putri; M. Dzikrul Hakim Al Ghozali (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2026)
This study investigates the use of Duolingo as a digital learning medium to improve Arabic writing skills (maharah kitabah), particularly vocabulary mastery and sentence structure accuracy. A qualitative descriptive design was employed to explore students’ writing development during Duolingo-assisted learning. Data were obtained from students’ writing products before and after using Duolingo, classroom observations, semi-structured interviews, and supporting documents. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, conclusion drawing, content analysis, and error analysis. The findings show that Duolingo contributes positively to Arabic writing development by increasing vocabulary diversity, improving word-choice accuracy, activating previously passive vocabulary, and strengthening the use of thematic vocabulary. Students also demonstrated better mastery of Arabic sentence structures, particularly jumlah ismiyyah and jumlah fi‘liyyah, as reflected in reduced grammatical errors and improved sentence coherence. However, Duolingo remains limited in developing higher-order writing skills, such as idea organization and contextual written expression, which still require teacher guidance. The novelty of this study lies in examining Duolingo’s contribution to Arabic writing through vocabulary mastery and sentence structure accuracy. The findings provide empirical evidence that digital learning applications can effectively complement Arabic writing instruction and support technology-enhanced language learning.